MPS I and Challenges of Diagnosis and Management of Genetic Disease in Resource Constraint Developing Country (Bangladesh Journal of Radiology and Imaging, 2026)
Emerging of Genetic disease like mucoplysaccharidosis is a concern matter of public health now a days. Developing country like Bangladesh has no comprehensive epidemiological data on the prevalence of most of the genetic disease. A case of 3-year-old child having characteristic facial and radiological features of MPS has been discussed and obstacles regarding diagnosis & management of the phenotypes are also highlighted. It is a high time to commence proper genetic service facilities in developing country like Bangladesh